FEM analyses for influences of stress-chemical solution on THM coupling in dual-porosity rock mass - Zhang, Yu-jun; Yang, Chao-shuai (Journal of Central South University, 2012)
The models of stress corrosion, pressure solution and free-face dissolution/precipitation were introduced. Taking a hypothetical nuclear waste repository in an unsaturated dual-porosity rock mass as the calculation objective, four cases were designed: 1) the fracture aperture is a function of stress corrosion, pressure solution and free-face dissolution/precipitation; 2) the fracture aperture changes with stress corrosion and pressure solution; 3) the fracture aperture changes with pressure solution and free-face dissolution/precipitation; 4) the fracture aperture is only a function of pressure solution, and the matrix porosity is also a function of stress in these four cases. Then, the corresponding two-dimensional FEM analyses for the coupled thermo-hydro-mechanical processes were carried out. The results show that the effects of stress corrosion are more prominent than those of pressure solution and free-face dissolution/precipitation, and the fracture aperture and relevant permeability caused by the stress corrosion are only about 1/5 and 1/1000 of the corresponding values created by the pressure solution and free-face dissolution/precipitation, respectively. Under the action of temperature field from released heat, the negative pore and fracture pressures in the computation domain rise continuously, and are inversely proportional to the sealing of fracture aperture. The vector fields of flow velocity of fracture water in the cases with and without considering stress corrosion are obviously different. The differences between the magnitudes and distributions of stresses within the rock mass are very small in all cases.